2016
DOI: 10.1128/genomea.00315-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of 37 Salmonella enterica Strains Isolated from Poultry Sources in Nigeria

Abstract: Here, we report the availability of draft genomes of several Salmonella serotypes, isolated from poultry sources from Nigeria. These genomes will help to further understand the biological diversity of S. enterica and will serve as references in microbial trace-back studies to improve food safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Also S. Typhimurium, which is commonly associated with poultry [54], was not observed in this study. This confirms observations by Fagbamila et al, (2017) and Useh et al, (2016) that these two serotypes play marginal role in the poultry industry in Nigeria. S. Kentucky was the most commonly observed serotype.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Also S. Typhimurium, which is commonly associated with poultry [54], was not observed in this study. This confirms observations by Fagbamila et al, (2017) and Useh et al, (2016) that these two serotypes play marginal role in the poultry industry in Nigeria. S. Kentucky was the most commonly observed serotype.…”
Section: Plos Onesupporting
confidence: 91%
“…A high number of Salmonella serotypes were observed in the farms investigated suggesting either a wide diversity of sources for introduction of Salmonella into the farms, or that common sources (such as contaminated feed) can contain different serotypes over time. Reports from other countries have also showed diversity in serotypes of non- typhoidal Salmonella in poultry farms [ 41 , 42 , 50 52 ]. Notably, S .…”
Section: Discussionmentioning
confidence: 99%
“…While there is paucity of information on the pathogenicity of some of the Salmonella serotypes identified in the present study, the availability of draft genomes of these serotypes have earlier been reported. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Stocked culture of Salmonella enterica serovar Zega originally isolated from commercial layers in South-western Nigeria, identified at the Department of Veterinary and Biomedical Sciences, South Dakota State University, Brookings, South Dakota, USA [9] and maintained at the bacterial bank, Bacterial Research Department, National Veterinary Research Institute, Vom, Nigeria was used in this study.…”
Section: Bacterial Isolate Used In the Studymentioning
confidence: 99%
“…Salmonella enterica serovar Zega, one of the over 3000 identified strains of salmonella were first isolated from dead ducklings in the Belgian Congo (now Democratic Republic of Congo) in 1952 [8]. Recently, it was listed amongst 37 Salmonella enterica strains isolated from commercial layer flocks in Southwest Nigeria [9] [10]. This suggests that the agent may be pathogenic for avian species.…”
Section: Introductionmentioning
confidence: 99%